Controlled Fabrication of Hierarchically Structured Nitrogen‐Doped Carbon Nanotubes as a Highly Active Bifunctional Oxygen Electrocatalyst. (18th January 2017) - Zhao, Xianglong; Li, Feng; Wang, Ruining; Seo, Jeong‐Min; Choi, Hyun‐Jung; Jung, Sun‐Min; Mahmood, Javeed; Jeon, In‐Yup; Baek, Jong‐Beom
Abstract : Hierarchically structured nitrogen‐doped carbon nanotube (NCNT) composites, with copper (Cu) nanoparticles embedded uniformly within the nanotube walls and cobalt oxide (Co x O y ) nanoparticles decorated on the nanotube surfaces, are fabricated via a combinational process. This process involves the growth of Cu embedded CNTs by low‐ and high‐temperature chemical vapor deposition, post‐treatment with ammonia for nitrogen doping of these CNTs, precipitation‐assisted separation of NCNTs from cobalt nitrate aqueous solution, and finally thermal annealing for Co x O y decoration. Theoretical calculations show that interaction of Cu nanoparticles with CNT walls can effectively decrease the work function of CNT surfaces and improve adsorption of hydroxyl ions onto the CNT surfaces. Thus, the activities of the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) are significantly enhanced. Because of this benefit, further nitrogen doping, and synergistic coupling between Co x O y and NCNTs, Cu@NCNT/Co x O y composites exhibit ORR activity comparable to that of commercial Pt/C catalysts and high OER activity (outperforming that of IrO2 catalysts). More importantly, the composites display superior long‐term stability for both ORR and OER. This simple but general synthesis protocol can be extended to design and synthesis of other metal/metal oxide systems for fabrication of high‐performance carbon‐based electrocatalysts with multifunctional catalytic activities. Abstract : Nitrogen‐doped carbon nanotubes (NCNTs), with copper (Cu) nanoparticles embedded uniformly within their walls and cobalt oxide (Co x O y ) nanoparticles decorated on their surfaces, are controllably synthesized via a rationally designed multistep procedure. The resultant Cu@NCNT/Co x O y composites exhibit electrocatalytic activity comparable to that of commercial Pt/C catalysts for the oxygen reduction reaction and activity higher than that of IrO2 catalysts for the oxygen evolution reaction.